2022
DOI: 10.1111/mec.16415
|View full text |Cite
|
Sign up to set email alerts
|

Combining population genomics with demographic analyses highlights habitat patchiness and larval dispersal as determinants of connectivity in coastal fish species

Abstract: Gene flow shapes spatial genetic structure and the potential for local adaptation.Among marine animals with nonmigratory adults, the presence or absence of a pelagic larval stage is thought to be a key determinant in shaping gene flow and the genetic structure of populations. In addition, the spatial distribution of suitable habitats is expected to influence the distribution of biological populations and their connectivity patterns. We used whole genome sequencing to study demographic history and reduced repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 90 publications
2
24
0
Order By: Relevance
“…The structuring effect of this oceanographic feature in species with early life stages is also corroborated when comparing with species without such stages. A recent study showed that for the broadnosed pipefish ( Syngnathus typhle ), which gives birth to live young, this barrier effect is less pronounced, and that genetic divergence is likely due to habitat effect and isolation by distance (Knutsen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The structuring effect of this oceanographic feature in species with early life stages is also corroborated when comparing with species without such stages. A recent study showed that for the broadnosed pipefish ( Syngnathus typhle ), which gives birth to live young, this barrier effect is less pronounced, and that genetic divergence is likely due to habitat effect and isolation by distance (Knutsen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic structuring of marine populations and adaptive differentiation has been shown to evolve despite high dispersal potential as a result of the interplay of environment, life history, and other factors influencing survival. Many marine taxa have life histories that feature pelagic egg and/or larval stages, enabling current-mediated dispersal across large distances which is thought to contribute to the low levels of genetic structuring often observed in marine fish (Levin 1996; Waples 1998; Juanes 2007; Knutsen et al . 2022).…”
Section: Introductionmentioning
confidence: 99%
“…2022), and whole genome resequencing approaches (Han et al . 2020; Knutsen et al . 2022) have with increasing levels of detail revealed significant climate or environmental associations that localize to discrete genomic regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations